The Role of Financial Technology (Fintech) in Enhancing Financial Inclusion Among MSMEs - Is Purwati; Rachmad Ilham; Dini Ayu Pramitasari (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
The growing significance of financial technology (fintech) has reshaped how micro, small, and medium enterprises (MSMEs) access financial services, particularly in developing countries. This study explores the role of fintech in enhancing financial inclusion among MSMEs by investigating the influence of fintech adoption, digital literacy, and financial literacy, while considering the moderating role of government regulation. Using a descriptive qualitative approach, data were collected through semi structured in depth interviews with MSME owners, fintech service providers, and financial regulators in both urban and rural regions. Thematic analysis revealed that fintech significantly improves MSMEs' access to financial services, but its effectiveness depends largely on the users' digital and financial competencies. Additionally, inclusive regulatory frameworks facilitate broader adoption and trust in fintech. The study highlights the interplay between technology, education, and institutional context in driving inclusive financial systems. Findings suggest that policies aimed at expanding digital and financial literacy, alongside adaptive regulation, are critical to maximizing fintech's inclusive potential. This research offers valuable insights for policymakers, fintech developers, and scholars interested in advancing digital financial inclusion in emerging economies.